The Relationship between Levels of Gender and Ethnic Group Representation - Ruedin, Didier (My University, 2010)
This article examines the relationship between levels of gender representation and levels of ethnic group representation in national parliaments. Taagepera (1994) and Lijphart (1999) predicted that because of shared mechanisms and covariates levels of representation in the two forms should be positively correlated. Whilst this paper can identify a number of shared covariates, there is no evidence of an association between levels of gender and ethnic group representation. The lack of negative association suggests that increasing levels of representation in one form does not necessarily come at the cost of the other. Instead it appears that the salience and politicisation of divisions – approximated by the make-up of society – may shape the relationship between levels of gender and ethnic group representation: representation scores tend to be higher in the forms of representation that are thought to be more salient.
Keywords: Development; Dynamic; Time; Model; Subjectivity; Sociocultural psychology